Draft Genome Sequence of Brucella abortus BCB027, a Strain Isolated from a Domestic Deer - Wang, Lulu (American Society for Microbiology, 2013)
Many Brucella species are isolated from nonpreferred hosts, and these bacteria may show genetic differences from isolates from the preferred hosts. Here, we report the draft genome sequence of Brucella abortus BCB027, a novel strain isolated from a domestic deer.